An Analysis of Urf in the Betawi Traditional Wedding Procession Tradition in Cibening Village, Bintara Jaya Village, West Bekasi District, Bekasi City. - Zanah, Miftahul (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This writing aims to find out how the wedding traditions commonly carried out by the Betawi indigenous people and the factors of acculturation and cultural assimilation of various wedding processions, both during the pre-wedding, and on the day of the wedding procession that took place. Is there any relation to 'urf that contradicts the nash from each traditional wedding procession held by the indigenous community concerned. This research is categorized as field research with qualitative methods. This writing is based on direct observation in the field and also interviews with indigenous Betawi people. In collecting data and information obtained, the author uses a sample with a snowball technique so that the information obtained is comprehensive and able to explore the Betawi cultural customs which in this case are related to the tradition of the wedding procession. In conclusion, the author found that there is a link in every tradition of the Betawi traditional community's wedding procession that is related to the texts that underlie the implementation of some of the processions that take place. The nash can be sourced from the Qur'an, Hadith as well as Ijma' and Qiyas of the scholars